GRANITIC MAGMATISM OF GRENVILLIAN AND LATE NEOPROTEROZOIC AGE IN FINNMARK, ARCTIC NORWAY - CONSTRAINING PRE-SCANDIAN DEFORMATION IN THE KALAK NAPPE COMPLEX - Kirkland C.L.; Daly J.S.; Whitehouse M.J. (My University, 2006)
The Caledonian Orogen in Arctic Norway is characterized by a variety of nappes thrust from west to east onto the Baltic Shield. Traditionally, this has been regarded as the product of two orogenic events: an earlier Finnmarkian (540-490 Ma) and a later Scandian event (400-425 Ma). However, ion microprobe U-Pb zircon dating of discordant plutonic rocks within the lowermost nappes demonstrates that some of the deformation must have taken place in a Grenville (Sveconorwegian) event. This view is supported by the 981 ± 7 Ma, 978 ± 9 Ma and 973 ± 4 Ma ages of the Repvåg, Hårvika and Siedgoaivi adamellite bodies. These bodies cut the Sørøy Succession, apparently after an earlier deformation event. On these grounds a Grenville (Sveconorwegian) event is responsible for the D2 deformation within the Olderfjord and Kolvik nappes. Within the overlying Havvatnet Imbricate Stack, early deformation took place in the Neoproterozoic, "Porsanger Orogeny". Evidence for this event is provided by the Litlefjord and Revsneshamn adamellite bodies dated at 841 ± 6 Ma and 839 ± 10 Ma and pegmatitic intrusions, dated at 826 ± 6 Ma and 833 ± 9 Ma, which show clear discordant structural relationships cutting F2 fold structures that affect the Klubben Psammite, the oldest unit of the Sørøy Succession. Within the uppermost nappe (Sørøy- Seiland nappe) syn-deformational migmatitic leucosomes in the Eidvågeid Paragneiss yield crystallization ages of 709 ± 4 Ma. This age is indistinguishable from zircon overgrowths within the underlying Havvatnet Imbricate Stack. Hence, juxtaposition of these nappes predates Scandian tectonism and occurred during the Snøfjord event at c. 710 Ma. The component nappes of the KNC show decreasing ages of anatexis on moving up the nappe pile. Such temporal and spatial patterns are consistent with episodic terrane amalgamation from Grenvillian times. The KNC provides evidence for punctuated crustal anatexis and episodic orogenic deformation of c. 980 Ma (Grenvillian-Sveconorwegian), c. 840 Ma (Porsanger) and c. 710 Ma (Snøfjord) age, overprinted by intense Scandian deformation. These data support the notion of a Grenville segment extending between Greenland and Baltica and require a radical revision to the tectonometamorphic evolution of the KNC. The KNC represents a collage of exotic, diachronously accreted, terranes overthrust by Llandovery flysch of Laurentian affinity. © 2005 Elsevier B.V. All rights reserved.
Keywords: CALEDONIDES; FINNMARKIAN; GRENVILLIAN; KALAK NAPPE COMPLEX; PORSANGER; SøRøY SUCCESSION; SCANDIAN; SNøFJORD; SVECONORWEGIAN; Neoproterozoic; Llandovery; Precambrian::Proterozoic::Neoproterozoic; Докембрий::Протерозой::Неопротерозойская; Paleozoic::Silurian::Llandovery; Палеозой::Силурийская::Лландоверийский